Mast cell–neuron axis as a core mechanism in chronic pruritus of atopic dermatitis: from mechanistic insights to therapeutic targets - Li, Dongdong; Han, Yusheng; Zhou, Jingjing; Yang, Huasen; Chen, Jing; Tey, Hong Liang; Tan, Timothy T. Y. (Frontiers in Immunology, 2025)
Chronic pruritus is a defining and therapeutically challenging symptom of atopic dermatitis (AD). Recent advances highlight the mast cell–neuron axis as a central neuroimmune interface orchestrating bidirectional crosstalk between the immune and peripheral nervous systems. Skin mast cells located in close proximity to sensory nerve endings release pruritogenic and neuroregulatory mediators, including histamine, tryptase, and nerve growth factor (NGF), and also modulate IL-31 signaling pathways. These mediators act on neuronal receptors such as IL-31RA, protease-activated receptors 1/2 (PAR-1/2), TrkA, and the adenosine triphosphate (ATP)-gated P2X3 receptor, thereby enhancing neuronal excitability and sensitizing transient receptor potential (TRP) channels (TRPV1, TRPA1). Conversely, sensory neurons release neuropeptides, among which substance P (SP) has been clearly demonstrated to activate Mas-related G protein–coupled receptor X2 (MRGPRX2) on mast cells, inducing non-IgE-mediated degranulation, whereas calcitonin gene-related peptide (CGRP) primarily regulates vascular tone and inflammation, with its direct role in MRGPRX2 activation remaining under investigation. This bidirectional interaction drives a feed-forward itch–inflammation loop. This circuit is further amplified by epidermal barrier dysfunction, microbial dysbiosis, type 2 immune polarization, and neurovascular remodeling. Structural adaptations–including intraepidermal nerve fiber branching and synapse-like mast cell–neuron junctions–provide anatomical substrates for chronic peripheral sensitization. While IL-31RA antagonists such as nemolizumab have demonstrated clinical efficacy, emerging targets like MRGPRX2 and TRPV1/TRPA1 channels offer additional therapeutic avenues but face challenges in translation and safety. Moreover, the P2X3 receptor has been proposed as a potential target for neurogenic itch in AD, but current research remains at an early stage and lacks direct clinical validation, highlighting limitations in its therapeutic development. This review provides a comprehensive mechanistic synthesis of the mast cell–neuron axis in AD-associated pruritus, critically evaluates current and investigational therapies, and explores the potential of multi-target interventions, including traditional Chinese medicine (TCM), for axis-level modulation. These efforts support the advancement of precision therapies targeting neuroimmune circuits in chronic inflammatory dermatoses.